The N-terminal domain plays a crucial role in the structure of a full-length human mitochondrial Lon protease - Kereïche, Sami; Kováčik, Lubomír; Bednár, Jan; Pevala, Vladimír; Kunová, Nina; Ondrovičová, Gabriela; Bauer, Jacob; Ambro, Ľuboš; Bellová, J; Kutejová, Eva; Raška, Ivan (Scientific reports, 2016)
Lon is an essential, multitasking AAA(+) protease regulating many cellular processes in species across all kingdoms of life. Altered expression levels of the human mitochondrial Lon protease (hLon) are linked to serious diseases including myopathies, paraplegia, and cancer. Here, we present the first 3D structure of full-length hLon using cryo-electron microscopy. hLon has a unique three-dimensional structure, in which the proteolytic and ATP-binding domains (AP-domain) form a hexameric chamber, while the N-terminal domain is arranged as a trimer of dimers. These two domains are linked by a narrow trimeric channel composed likely of coiled-coil helices. In the presence of AMP-PNP, the AP-domain has a closed-ring conformation and its N-terminal entry gate appears closed, but in ADP binding, it switches to a lock-washer conformation and its N-terminal gate opens, which is accompanied by a rearrangement of the N-terminal domain. We have also found that both the enzymatic activities and the 3D structure of a hLon mutant lacking the first 156 amino acids are severely disturbed, showing that hLon's N-terminal domains are crucial for the overall structure of the hLon, maintaining a conformation allowing its proper functioning.
Keywords: Bacillus subtilis; adenosintrifosfát; lidé; Image Processing, Computer-Assisted; Humans; proteolýza; Protein Domains; proteasa La; Protease La; Adenosine Triphosphate; mitochondrie; Adenylyl Imidodiphosphate; Mutant Proteins; počítačové zpracování obrazu; adenylylimidodifosfát; Mitochondria; Proteolysis; mutantní proteiny; proteinové domény